8 Employment circumstances and chemical control measures provided to workers with dermal exposure to chemicals - results from a population-based survey. (11th October 2013) - MacFarlane, E; Smith,; Keegel,
Abstract : Objective: Chemical exposures in workplaces are an important occupational health and safety problem; however, there is little published information available about the provision of basic exposure controls to workers with dermal chemical exposures across industrial sectors. This analysis investigated relationships between occupational, workplace and demographic factors and the provision of personal protective measures and/or provision of administrative controls among survey respondents exposed to chemicals at work. Methods: The inaugural Australian National Hazard Exposure Worker Surveillance (NHEWS) survey was a large, population-based telephone survey of workers from all industries. Respondents who reported dermal chemical exposure at work were asked about protective measures provided to them in the workplace, which we classified as administrative measures or personal protective measures. An ordered logistic model was used to investigate the odds of having chemical exposure protections provided by workplace and demographic variables. Results: Workplace size was the strongest predictor for the provision of exposure protection systems incorporating both administrative measures and personal protective measures. Compared to workplaces with fewer than five employees, workers in workplaces with 200 or more employees were more likely to have more comprehensive exposure protection systems, incorporating both administrative and personal protective measures (OR 4.96, 95%CI 2.97–8.28). Permanent and fixed-term employment was also associated with more comprehensive exposure protection systems compared with temporary/casual employment (OR 1.56, 95% CI 1.09–2.22) and self-employment (OR 1.69, 95% CI 1.18–2.42). Conclusion: In the NHEWS survey, employment in small workplaces, non-permanent and self-employment arrangements were associated with less comprehensive exposure protection systems. This suggests that small workplaces and non-permanent or self-employed workers may be important intervention targets for improving workers' exposure protection. Further research investigating exposure control provision in small workplaces and among insecurely employed workers as well as evaluation research of interventions to reach these workers is recommended.